On the Neotropical species of the spider genus Tekellina Levi, 1957 (Arachnida: Araneae: Synotaxidae) - Estol, Narelle; Valiati, Victor Hugo; Brescovit, Antonio D.; Rodrigues, Everton Nei Lopes [UNESP] (Museum National D'Histoire Naturelle, 2024)
The genus Tekellina Levi, 1957 is currently composed of ten species, six of which are Neotropical. They are small-sized spiders (0.9 to 1.5 mm), with a wide distribution, with a great diversity in the Neotropical Region and well represented in Brazil. In this article, males and females of the species Tekellina bella Marques & Buckup, 1993 and T. crica Marques & Buckup, 1993 are redescribed and illustrated. The female of Tekellina minor Marques & Buckup, 1993 is described and illustrated for the first time. New records are included for Neotropical species. Tekellina guaiba Marques & Buckup, 1993 is synonymized with T. pretiosa Marques & Buckup, 1993. Three new species are described for Brazil: Tekellina picurrucha Rodrigues & Estol sp. nov. (São Paulo, Paraná and Rio Grande do Sul), Tekellina miuda Rodrigues & Estol sp. nov. (São Paulo and Paraná) and Tekellina miudinha Rodrigues & Estol sp. nov. (São Paulo). Distribution maps with new records and an identification key of the Neotropical species are also presented.
Keywords: new records; New species; new synonymy; taxonomy